AKIBAT HUKUM TERHADAP KREDITUR DALAM PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG BERDASARKAN UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Rezki Saputra Jas; Yeni Triana; Indra Afrita (Yustitia, 2025)
The Postponement of Debt Payment Obligations (PKPU) filed by a creditor is a legal mechanism that allows a creditor to file a PKPU petition against a debtor suspected of experiencing financial difficulties and failing to meet their debt payment obligations on time. The purpose of this study is to examine the legal consequences for creditors in the Postponement of Debt Payment Obligations based on Law Number 37 of 2004 on Bankruptcy and the Postponement of Debt Payment Obligations and the judges’ considerations in deciding on the PKPU petition. This study employs a normative legal research method. The data sources are derived from secondary data, categorized into three types: primary legal materials, secondary legal materials, and tertiary legal materials. The data collection technique used is documentary study or literature review. The conclusion of this research indicates that the legal consequences of a judge rejecting a PKPU petition include: First, the rejection of the petition means that no Postponement of Debt Payment Obligations (PKPU) is granted to the debtor. Second, if a creditor wishes to sue the debtor again regarding debt fulfillment, the creditor can file a civil lawsuit for default. The judge’s considerations in rejecting the PKPU petition are based on the fact that the debtor does not have more than one creditor because other creditors lack valid power of attorney. Furthermore, in cases where the amount of debt is insignificant and insufficient to trigger bankruptcy if the peace plan under the PKPU fails to materialize, this also influences the court’s decision. The study recommends that there should be clearer regulations concerning the position of other creditors and the minimum debt amount in the Bankruptcy and Postponement of Debt Payment Obligations Law. Legal considerations should also adopt a dimension of fairness, strict legal protection, and substantive legal breakthroughs to ensure the enforcement of law that is beneficial for human needs.